Contributions to the Knowledge of Sexual Dimorphism in Liolaemus darwinii (Squamata, Liolaemidae) in the Monte Desert of Argentina - Castillo, Gabriel Natalio (2021)
The lizard Liolaemus darwinii (Liolaemidae) is a typical species with wide distribution in Monte environments of Argentina. The objective of this study is contribute to knowledge of sexual dimorphism in a population of L. darwinii (Bell, 1843). We evaluated sexual shape variation of the cephalic region through procustes analyses with geometric morphometry. We predict that the heads in males will have diff erences in shape with respect to females. The results showed signifi cant sexual diff erences in shape, mainly in the region around the eyes. There were no signifi cant differences in sizes. Geometric morphometry analyses are a useful tool for addressing sexual differences in Monte lizards. This constitutes the first study for the center-west of Argentina in San Juan province that implements these geometric morphometry analyses.